THE MOTHER–CHILD ATTACHMENT PARTNERSHIP IN EARLY CHILDHOOD: SECURE BASE BEHAVIORAL AND REPRESENTATIONAL PROCESSES. Issue 4 (5th December 2018) - Vaughn, Brian E.
Abstract : The chapters in this monograph describe the transition of attachment representations from a predominantly sensorimotor, in the moment, experience for the infant/toddler to internalized, mental representations of attachment that are transportable to new social contexts, in which attachment figures may not be present. The chapters focus on means that parents use to help their child effect this transition in terms of both behavioral support for the child's secure base behavior and for cognitive skills that underlie the child's construction of mental models of attachment. The results cohere across studies and make a compelling case for Bowlby's notion that internal models of how attachment "works" are co‐constructed through social processes during early childhood. Taken together, the results reported here constitute a milestone achievement for the attachment enterprise in terms of their theoretical and methodological rigor. These findings also justify Bowlby's confidence that cognitive psychology would become a critical disciplinary ally of attachment theory.